Efficiency of nitrogen fertilizers for rice : (International rice research institute, 1987)
This volume contains 19 papers on soil fertility and organic and inorganic fertilizer evaluation for rice that given at the meeting, which was held 10 -16 April 1985 at the CSIRO Division of Irrigation Research, Griffith, New South Wales.